A multidisciplinary handbook of child and adolescent mental health for front-line professionals - Dogra, Nisha, 1963- (Jessica Kingsley Publishers, 2018)
A fully updated version of the successful second edition, this book provides an accessible introduction to child mental health, covering the nature, prevalence, treatment and management of mental health problems in children and young people.